"Getting stuck in": body work and physical capital in non-traditional occupations. Issue 7 (25th August 2022) - Murphy, Caroline; O'Meara, Aoife
Abstract : Purpose: Drawing on Bourdieu's conceptualisation of physical capital, this article explores the experiences of male and female employees in non-traditional occupations where body work is an integral part of the role. Specifically, the authors examine how being an underrepresented gender in this context impacts the experience of work, including challenges faced and perceptions for future opportunities in the role. Design/methodology/approach: The research is based on two in-depth case studies undertaken in the social care and security/door work sector. Semi-structured interviews were conducted with male social care workers and female security workers in the night-time hospitality sector. Management representatives were also interviewed in each case. The interviews examined how the nature of the work in these roles impacted on the underrepresented gender's perceptions of various aspects of their working lives. Findings: The findings illustrate how many of the challenges associated with non-traditional occupations are experienced differently in body work roles, either being amplified or instead presenting opportunities for the role holder with implications for the day-to-day and longer-term experience of work. The findings illustrate how the actions and behaviour of management and colleagues can exacerbate the extent to which underrepresented gender feel accepted within their role and organisation. Practical implications: Organisational decision makers need to be aware of the importance of reviewing practices regarding hiring, promotion and the allocation of tasks and duties for non-traditional role holders engaged in body work. Originality/value: The article contributes to understandings of "body work" and physical capital in non-traditional occupations, illustrating how gender-based assumptions can restrict individuals in these roles to a greater extent than in other forms of work where the body is salient to the performance of the role.